VISUAL REPRESENTATION OF THE FEMALE GAZE IN âLADY BIRDâ MOVIE - Rike P, Eudia
Based on exploring the reverse of Laura Mulvey’s theory in 1975, the Male gaze, this paper attempts to breakdown how does the female gaze visually shown in movies that is made by women. Male gaze theory suggests that the male gaze denies women’s human identity, making the status of object to be only admired for physical or sexual appearance. In contrary, female gaze theory suggest that the female gaze denies women as the object of physical or sexual appearance and men’s sub-ordinat. The movie “Lady Bird” (2017) was chosen since it was one of the critically acclaimed movies that was written and directed by a woman director, Greta Gerwig in the last few years. “Lady Bird” was a coming- of-age movie that centered along the ups and downs relationship between the mother and her daughter. With using qualitative analysis methodology, “Lady Bird” through its scenes were analized by the mise-en-scène, including setting, facial expression and gesture, lighting, and costume, along cinemaography theory of Amy Villarejo and through Terry Barret’s art critics method, will be examined the visual aspects of Joey Soloway’s concept of Female Gaze (2016). From this research, it is found that there are several visual aspects indicating "Lady Bird" movie represents the first point of Soloway's gaze, which is to reclaim the body with the intention to communicate Feeling Seeing. Feminine elements and women's daily life are crucial aspects in the movie. Cinematography brings the audience closer without being intrusive, and doesn’t objectify women. Gestures of each female character enrich their personality and feelings.